1998
DOI: 10.1109/10.661154
|View full text |Cite
|
Sign up to set email alerts
|

A statistical method for the measurement of muscle activation intervals from surface myoelectric signal during gait

Abstract: The aim of this work is to present an original double-threshold detector of muscle activation, specifically developed for gait analysis. This detector operates on the raw myoelectric signal and, hence, it does not require any envelope detection. Its performances are fixed by the values of three parameters, namely, false-alarm probability (Pfa), detection probability, and time resolution. Double-threshold detectors are preferable to single-threshold ones because, for a fixed value of the Pfa, they yield higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
248
0
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 330 publications
(255 citation statements)
references
References 18 publications
3
248
0
4
Order By: Relevance
“…For future work, we intend to add new important features for the EMG analysis, different types of activation detection algorithms (e.g. double-threshold detector Bonato et al, 1998 or adaptive threshold methods), simultaneously run the activations detection algorithm for all measured EMG signals and allow for individual preferences in the signal filtering steps before applying the activation detection operations. We also aim to perform more tests with the developed algorithms, not only for accuracy and speed performance, but also concerning the possibility of adding noise to the EMG signals and analyze the influence in the detected activations.…”
Section: Discussionmentioning
confidence: 99%
“…For future work, we intend to add new important features for the EMG analysis, different types of activation detection algorithms (e.g. double-threshold detector Bonato et al, 1998 or adaptive threshold methods), simultaneously run the activations detection algorithm for all measured EMG signals and allow for individual preferences in the signal filtering steps before applying the activation detection operations. We also aim to perform more tests with the developed algorithms, not only for accuracy and speed performance, but also concerning the possibility of adding noise to the EMG signals and analyze the influence in the detected activations.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, we can characterize a fixation by applying explicit spatial and temporal criteria. We can detect a fixation if the eye remains within a radius of 1° during a temporal fixation threshold of 200 ms, which is the de facto standard [19]. The gaze-tracking system measures eye-movement spatial dispersion and speed to infer fixation status (Figure 2(a)) and differentiate between fixation and saccadic movements of the eye.…”
Section: Video-oculographic Systemmentioning
confidence: 99%
“…We selected the activation detection algorithm after an evaluation study of some of the available algorithms. We compared six different algorithms, namely, Hodges and Bui [36], Bonato et al [19], Lidierth [37], Abbink et al [38], and approximated generalized likelihood ratio (AGLR) step and AGLR ramp [39].…”
Section: Electromyographic Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…A comparative study regarding several methods for EMG signals onset detection, including those proposed by Hodges (Hodges and Bui, 1996) and Bonato (Bonato et al, 1998), is reported by Staude (Staude et al, 2001). Another possible application is related to the detection of general transient events.…”
Section: Introductionmentioning
confidence: 99%